Pengaruh Terapi Mckenzie terhadap Tingkat Nyeri dan Tekanan Darah pada Pasien Hipertensi - Muhammad Affiz Zaman; Indah Sri Wahyuningsih; Retno Setyawati (Journal of Medical Practice and Research, 2026)
Background : Hypertension is a major health problem often accompanied by musculoskeletal pain. The Mckenzie technique is commonly used to reduce pain, but its effect on blood pressure remains unclear. Purpose : To determine the effect of Mckenzie therapy on pain intensity and blood pressure in hypertensive patients. Methods : This study used a quasi-experimental design with a One Group Pretest–Posttest approach involving 18 respondents. Pain levels were measured using the Numerical Rating Scale (NRS) and blood pressure was measured directly. Data were analyzed using the Wilcoxon test. Results:Mckenzie therapy significantly reduced pain (p = 0.005). However, it did not produce a significant change in blood pressure (p = 0.157). Conclusion : Mckenzie therapy is effective in reducing pain, but does not significantly affect blood pressure within the study duration.